Virtual Yoga as an Innovative Approach to Cancer Patient Care: Evidence and Opportunities - Giridharan, Selvaraj (International Research Journal of Ayurveda & Yoga, 2024)
Introduction: Virtual yoga has gained attention as an accessible intervention to support cancer patients in managing symptoms, such as pain, fatigue, anxiety, and depression. However, its efficacy and feasibility compared to in-person sessions remainunclear. Methods: A literature review was conducted using PubMed, the Cochrane Library, Scopus, and Google Scholar. Studies from 2000 to 2024 that investigated the effects of virtual yoga interventions on patients with cancer were included in the study. The outcomes assessed were symptom burden, QoL, pain, fatigue, and patient adherence. Results: Four studies were identified that showed that virtual yoga led to moderate improvements in sleep disturbance, pain intensity, anxiety, depression, and fatigue among cancer patients. These studies also demonstrated the feasibility of virtual yoga, although adherence and access to technology posed challenges for some participants. Discussion: The results indicate that virtual yoga is a promising tool for improving physical and psychological outcomes in patients with cancer. However, challenges, such as the digital divide and patient engagement, need to be addressed. Further research, including large-scale trials, is required to confirm its efficacy and to integrate virtual yoga into standard cancer care protocols.